TORBANGUN (Coleus amboinicus) LEAF AS POTENTIAL NEWCOMER IN GALACTOGOGUE OR BREASTMILK BOOSTER: A NARRATIVE REVIEW - Yudhawan, Indra; Daniel, Vino; Cahyaningrum, Putri Khaerani; Fadlilah, Synta Haqqul; Suhartomo, Dalri Muhammad; Wahyudi, Ari; Putra, Akwila Albert Dakusha; Pratiwi, Intan Diah; Hawwin, Nur; Kurniawan, Dhadhang Wahyu (Mandala Of Health, 2025)
The postpartum period is a critical phase for infant development, and one of the challenges during this time is inadequate or absent lactation, which leads to insufficient breast milk (ASI) production. Baby’s growth and development require an adequate amount of nutrition, especially during 6 months of life. Breast Milk is the most fundamental food for babies, and offers complete nutrition for growth and development. However, some mothers are unable to produce enough breast milk for the baby and need to take supplements to stimulate their milk production. Torbangun or Bangun-bangun (Coleus amboinicus) leaf is empirically used to increase milk production in some areas of Indonesia. Although, the use of torbangun is not widely used and known. This research offers an investigation and review of many references to find out the current research on torbangun, especially in association with breast milk production. The result shows that there are quite a lot of research has been done related to torbangun in increasing breast milk. Torbangun has proven to have significant potential as a supplement for increasing breast milk production. The research is still in a preliminary study and there is still a few research that could elucidate the mechanism of action of torbangun as galactogogue, the accuracy of dosage, phytochemical compound, and its safety. Therefore, further research is strongly suggested to elucidate this aspect, especially in dosage, standardization, mechanism of action, scientific formulation, phytochemical compound along with its activity and its safety.